2018
DOI: 10.1111/liv.13977
|View full text |Cite
|
Sign up to set email alerts
|

Human beta‐defensin‐1 is a highly predictive marker of mortality in patients with acute‐on‐chronic liver failure

Abstract: Background & Aim Human beta‐defensin‐1 (hBD‐1) is a natural antimicrobial peptide expressed in the epithelia of multiple tissues including the digestive tract. In the current study, hBD‐1 levels were determined in different subsets of patients with decompensated cirrhosis including acute‐on‐chronic liver failure (ACLF). In addition, the association with mortality of hBD‐1, C‐reactive protein (CRP) and procalcitonin (PCT) was assessed. Methods A total of 125 patients were divided into three groups: 39 with ACLF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In turn, Zhong et al ( 97) reported that knock-out of a-defensins resulted in greater liver damage in a mouse model of alcoholic steatohepatitis, while administration of synthetic human adefensins 5 showed a therapeutic effect in this study. Mani et al (98) showed that the level of human b-defensin 1 was significantly elevated in patients with acute or chronic hepatic failure, indicating a strong predictive value as a marker of mortality. There are also reports indicating increased expression of a-defensin 4 in infections with hepatitis viruses, which, as described earlier, are associated with ALF.…”
Section: Defensins In Rabbitsmentioning
confidence: 99%
“…In turn, Zhong et al ( 97) reported that knock-out of a-defensins resulted in greater liver damage in a mouse model of alcoholic steatohepatitis, while administration of synthetic human adefensins 5 showed a therapeutic effect in this study. Mani et al (98) showed that the level of human b-defensin 1 was significantly elevated in patients with acute or chronic hepatic failure, indicating a strong predictive value as a marker of mortality. There are also reports indicating increased expression of a-defensin 4 in infections with hepatitis viruses, which, as described earlier, are associated with ALF.…”
Section: Defensins In Rabbitsmentioning
confidence: 99%
“…Another important application for MF-AMPs in human health is their roles as the biomarkers of several diseases both related and unrelated to infections [28][29][30][31]. In this Special Issue, Scnheider and collaborators summarized the biomarker profile of CgA and its derived antimicrobial peptides in the context of critically ill patients [4].…”
mentioning
confidence: 99%